KNOWLEDGE AND EFFECTIVENESS OF COVID-19 AND SUSTAINABLE NATIONAL DEVELOPMENT IN NASSARAWA-EGGON LOCAL GOVERNMENT AREA, NASARAWA STATE, NIGERIA - Usman, Ibrahim; Anjugu, Reuben Joseph (African Journal of Social and Behavioural Sciences, 2024)
One of the major components and indices of sustainable national development is sound health because only a healthy populace can contribute to any society's purposive development. Recent occurrences have threatened the health and wellbeing of Nigerian society, with the most recent being the COVID-19 pandemic. Pandemics, in general, are not merely serious public health concerns; instead, they give impetus to disastrous socioeconomic and political crises wherever and whenever they occur. COVID-19, in addition to being a cankerworm to the global public health of the century, is considered an indicator of a deficiency in social advancement. Despite many efforts by health institutions to prevent the spread and contraction of the deadly virus, the virus continues to spread, which poses a threat to sustainable national development. This study assessed the knowledge and effectiveness of COVID-19 prevention and sustainable national development in Nassarawa-Eggon LGA of Nasarawa State, Nigeria. Global risk society theory was adopted and used in this study. A survey design was used in the study, where a sample of 399 respondents was selected from a population of 169,449 using Yamane and Bowley’s sample selection formula. Furthermore, a multistage cluster sampling technique using clusters was adopted to select 5 political wards out of the 14 political wards in the Nassarawa-Eggon L.G.A. Questionnaire and in-depth interviews were used as the main instruments for data collection. This study revealed that knowledge from the media, peer groups, healthcare workers and religious leaders influences effective preventive measures against COVID-19 to ensure the sustainable development of Nassarawa-Eggon L.G.A. This study recommends the regulation of information disseminated from the media, the provision of only factual and concise information from appropriate and authorized bodies, and the indulgence of members of society in friendly and healthy conversations by health workers, which will increase people’s knowledge about how to prevent themselves from contracting diseases for sustainable national development in Nassarawa-Eggon, Nasarawa State and Nigeria.